2017
DOI: 10.1007/s00701-017-3399-2
|View full text |Cite
|
Sign up to set email alerts
|

Flexible endoscopically assisted evacuation of acute and subacute subdural hematoma through a small craniotomy: preliminary results

Abstract: The results reported here suggest that small craniotomy evacuation with a flexible endoscope is a safe, effective, and minimally invasive treatment for acute and subacute SDH in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Previous reports also stated that older patients appear to be good candidates for endoscopic evacuation. 9,17 An endoscopic approach may also be preferable in patients who cannot tolerate a larger craniotomy because of blood loss or other comorbidities or who could benefit from a shorter surgery. Patients with an enlarging SDH and associated brain contusions, who were excluded by Yokosuka et al, 9 may be eligible for the technique as long as bipolar cautery is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports also stated that older patients appear to be good candidates for endoscopic evacuation. 9,17 An endoscopic approach may also be preferable in patients who cannot tolerate a larger craniotomy because of blood loss or other comorbidities or who could benefit from a shorter surgery. Patients with an enlarging SDH and associated brain contusions, who were excluded by Yokosuka et al, 9 may be eligible for the technique as long as bipolar cautery is available.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible endoscopes were used to treat traumatic intracranial hemorrhages in the 1990s. 19 Recently, Kawasaki et al 17 reported application of a flexible endoscope for the evacuation of acute and subacute SDHs. One surgeon navigated the 5-mm flexible endoscope while a second surgeon removed the hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…It provides good visualization compared with the flexible scope. There are reports of use of both rigid [1][2][3][4]8,10,[12][13][14]17,19,21 and flexible scopes 5,9,11 in the management of CSDH. There may be difficulty in advancing the rigid scope, especially when the bony opening is not selected properly.…”
Section: Discussionmentioning
confidence: 99%
“… 14 36) And endoscopic removal of ASDH have been reported recently. 19 41 51 56 100) But, no well-designed comparative study or large case series is reported and clinical experiences are limited up to now. And also, indications for the endoscopic surgery have not been well established.…”
Section: Surgical Management Of Asdhmentioning
confidence: 99%
“…Flexible endoscope, even in low resolution, can be a good tool to get optimal and safe evacuation of the ASDH. 51) Endoscopic evacuation of traumatic ASDH will be a novel procedure as a minimally invasive surgery in appropriately selected cases.…”
Section: Surgical Management Of Asdhmentioning
confidence: 99%